Chlorogenic acid-Isolate from White Butterfly (Clerodendrum volubile P. Beauv) Leaf Scavenged Reactive Species and Inhibited α-Glucosidase, α-Amylase, and ACE-1: Pointer to Hypoglycemic and Cardioprotective Potentials - Ibukun, Oluwafemi; Oladipo, Martha; Oladipo, Gideon; Olorunfemi, Emmanuel; Ibiyemi, David; Elija-Afolabi, Temitope; Ogunlade, Oluwatimilehin (International Journal of Phytomedicine, 2025)
Chlorogenic acid is bioactive phenolic compound found in medicinal and nutritional plants, linked to several therapeutic relevance, making it a highly commercialized phenolic compound responsible for the economic relevance of the popular green tea. The white butterfly (Clerodendrum volubile P. Beauv) is an indigenous plant whose leaf is blended to make soup among the Ikale and Ijaw tribes, in Ondo State, Nigeria. The aim of this research is to isolate chlorogenic acid from the white butterfly leaf and determine the antioxidant, hypoglycemic and angiotensin-1 converting enzyme (ACE-1) inhibiting potentials as a rider to further studies on the chlorogenic acid fraction. White butterfly leaf was obtained and 80% ethanol was used to extract crude extract, the crude extract was further subjected to chromatographic screening over a 10 g Sephadex LH-20 column to elute fractions using 80 % ethanol as the mobile phase. The crude extract and the chromatographed fraction were characterized using HPLC. The Chromatographed fraction which is the chlorogenic acid isolate of white butterfly leaf (MLECS) was evaluated using biochemical analyses to determine its antioxidant properties, and inhibition of α-glucosidase and α-amylase activities, and ACE-1 activity. The characterization of the polyphenolic compounds revealed the presence of chlorogenic acid as the most predominant compound, while quercetin, ellagic acid, salicylic acid, p-hydroxybenzoic acid, and caffeic acid are in high amount. The chromatogram of the chlorogenic acid fraction showed a single high peak and the purity level of the chlorogenic acid isolate. The chlorogenic acid isolate demonstrated antioxidant properties, inhibited α-glucosidase, α-amylase and ACE-1 activities in a concentration dependent manner with varying IC50 values. The white butterfly leaf is nutritional and therapeutic with respect to the starch hydrolysis and angiotensin-II anabolism. The predominance of chlorogenic acid could increase the economic value as a commercial source of chlorogenic acid.